17β-Estradiol nongenomically induces vasodilation is enhanced by promoting phosphorylation of endophilin A2. (3rd August 2022) - Liu, Xiao-Yun; Li, Ping; Li, Xiao-Sa; Simoncini, Tommaso; Cheng, Yang
Abstract: Objective A previous study found that the tyrosine phosphorylation of endophilin A2 (Endo II) was responsible for increase surface expression of MT1-MMP and ECM degradation; however, there is little information about whether Endo II could influence membrane estrogen receptors (mERs) and its functions. Materials and methods In the present study, Human umbilical vein endothelial cells (HUVECs) were treated with E2, PPT, DPN, ICI 182780, Endo siRNA or negative control siRNA, and the biological behavior of the treated cells was observed. The mice were randomly divided into AAV-control-shRNA + Ach, AAV-Endo II-shRNA + Ach, AAV-control-shRNA + E2, AAV-Endo II-shRNA + E2 groups and the thoracic aorta were isolated, cut into 2-mm rings, then the wall tension was detected. Results We found that 17β-Estradiol (E2) enhanced mERα protein level, which was further increased after knocking down Endo II, the mechanism maybe involved in E2-induced tyrosine phosphorylation of Endo II. In addition, we also observed that Endo II blocked the activation of Akt, ERK1/2 and eNOS signaling in HUVECs treated with E2. E2 induced vasodilation was significantly increased by silencing of Endo II expression. Conclusion Our study provided a sound basis to selective modulate Endo II for E2's nongenomic pathway, which can be benefit for cardiovascular system.